Thermal analysis of epoxy resin matrix and carbon fiber epoxy laminate cured by imidazole - Chen, Shaojie; Xu, Yanying; Wang, Zhi (Journal of thermal analysis and calorimetry, 2022)
The epoxy composite cured by imidazole has better heat resistance. In this paper, the heat-driven mass loss process of epoxy resin matrix and carbon fiber epoxy laminate cured by 2E4MI, a kind of imidazole, were investigated by thermogravimetric analysis at different heating rates under nitrogen and air atmosphere. It was observed that the pyrolysis reactions of epoxy resin cured with imidazole and its carbon fiber epoxy laminate consist of one step in the nitrogen atmosphere, but in air atmosphere, their pyrolysis reactions consist of three and four steps, respectively. The glass transition temperature of 2E4MI cured epoxy resin was obtained around 143–150 °C and the variation of specific heat capacity with temperature was obtained between 20 and 230 °C. Furthermore, kinetic parameters for the pyrolysis of the samples were estimated using Kissinger and FWO method. The apparent activation energy and the apparent pre-exponential factor of 2E4MI cured epoxy resin were obtained around 165 kJ mol −1 and 4.85 × 10 8 in nitrogen, and these values in air were less. To carbon fiber epoxy laminate, these values were around 166 kJ mol −1 and 6.68 × 10 8 in nitrogen. It was shown that the thermal performance of the 2E4MI cured epoxy resin determined the thermal performance of the carbon fiber laminate to a large extent. So, the use of curing agent in epoxy resin indirectly determines the thermal properties of composites.